Dignity and Vulnerability Strength and Quality of Character. - Harris, George W. (University of California Press, 2020)
In this significant addition to moral theory, George W. Harris challenges a view of the dignity and worth of persons that goes back through Kant and Christianity to the Stoics. He argues that we do not, in fact, believe this view, which traces any breakdowns of character to failures of strength. When it comes to what we actually value in ourselves and others, he says, we are far more Greek than Christian. At the most profound level, we value ourselves as natur.